Cosmic War in Cyberspace: A Multimodal Analysis of Islamic State Posters on Social Media - Siti Aminah (Universitas Ahmad Dahlan, 2026)
This study extends multimodal discourse analysis by demonstrating how Arabic verbal texts and visual grammar jointly construct ideological representations in extremist propaganda posters. In particular, this article examines the verbal and non-verbal (visual) dimensions of the posters disseminated by the Islamic State (ISIS) through internet media, including Twitter, Facebook, Telegram, and YouTube. The data comprise posters released by the Islamic State and its affiliated organizations that circulate in cyberspace and are limited to Arabic-language posters. To uncover the dimensions of radicalism embedded in these posters, the study employs van Leeuwen’s multimodal analysis, treating each poster as a discourse approached through the perspectives of communicative events and the order of discourse. The analysis concludes that the propaganda posters employ a range of textual features, including the use of fi’l amr (imperative verbs), emphatic constructions, jumlah ismiyyah (nominal sentences), and jumlah fi’liyyah (verbal sentences). These propaganda posters are produced not only by the Islamic State itself but also by affiliated organizations such as al-Abd al-Faqir, al-Bawaba, and al-Furqan, with social media users as their intended audience both followers and the individuals or parties targeted by the propaganda. Through its posters, the Islamic State attempts to call for jihad, strengthen its existence, and spread terror among others.